Colonialism & violence in Zimbabwe a history of suffering - Schmidt, Heike Ingeborg (Boydell & Brewer, 2013)
Suffering, the experience of violation brought on by an act of violence or violent circumstances, is omnipresent in today's world - if only indirectly through global media representation. Despite this apparent immediacy, understanding how a person makes sense of his or her suffering tends to be fragmentary and often elusive. This book examines this key question through the lens of rural Zimbabwe and a frontier area on the border with Mozambique. It shows how African women, men, and children fashioned their life-worlds in the face of conflict. Historian Heike Schmidt challenges the apparently inseparable twin pairing of Africa and suffering. Even in situations of great distress, she argues, individuals and groups may articulate their social desires and political ambitions, and reforge their identities - as long as the experience of violence is not one of sheer terror. She emphasizes the crucial role women, chiefs, and youths played in the renegotiation of a sense of belonging during different periods of time. Based on sustained fieldwork, 'Colonialism and Violence' offers a compelling history of suffering in a small valley in Zimbabwe over the course of 150 years. Heike Schmidt is a Research Associate at the African Studies Centre, University of Oxford